The Effect of Compensation and Competence on The Performance of AD HOC Employees at The Ogan Ilir District Election Commission - Sofyan Sofyan; Marlina Widiyanti; Muhammad Yusuf; Agustina Hanafi (Jurnal Syntax Transformation, 2023)
This study was conducted to determine the effect of compensation and competence on the performance of ad hoc employees at the General Election Commission of Ogan Ilir district. The population in this study is all ad hoc employees of KDP for the 2024 election at the Ogan Ilir Regency KPU which amounts to 80 employees and 5 commissioners to measure employee performance. So the total population in this study is 85 employees and all of them are samples used in this study using the census method. The results of multiple linear regression analysis show that compensation and competence have a positive and significant effect on employee performance. Compensation, agencies can provide salaries that are differentiated based on the level of education of employees so that employees who have a higher level of education can have a more adjusted salary difference. Competence, the role of superiors in providing motivation and morale, in addition, the provision of material, direction or training in accordance with employee needs as a provision for employees in facing challenges and changes that occur.